Acute adaptations and subsequent preservation of strength and speed measures following a Nordic hamstring curl intervention: a randomised controlled trial. Issue 8 (18th April 2019) - Siddle, James; Greig, Matt; Weaver, Kristian; Page, Richard Michael; Harper, Damian; Brogden, Christopher Michael
ABSTRACT: This randomised controlled trial investigated changes in eccentric hamstring strength, 10m sprint speed, and change-of-direction (COD) performance immediately post Nordic hamstring curl (NHC) intervention and following a 3-week detraining period. Fourteen male team sports athletes were randomised to a do-as-usual control group (CG; n = 7) or to a NHC intervention group (NHC; n = 7). Isokinetic dynamometry at 180°/s evaluated eccentric hamstring strength immediately post-intervention as the primary outcome measure. Secondary outcomes included 10 m sprint time and COD. Each outcome was measured, pre, immediately post-intervention and following a 3-week detraining period. Immediately post-intervention significant group differences were observed in the NHC group for eccentric hamstring strength (31.81 Nm −1 vs. 6.44 Nm −1, P = 0.001), COD (−0.12 s vs. 0.20 s; P = 0.003) and sprint (- 0.06 s vs. 0.05 s; P = 0.024) performance. Performance improvements were maintained following a detraining period for COD (−0.11 s vs. 0.20 s; P = 0.014) and sprint (−0.05 s vs. 0.03 s, P = 0.031) but not eccentric hamstring strength (15.67 Nm −1 vs. 6.44 Nm −1, P = 0.145) These findings have important implications for training programmes designed to reduce hamstring injury incidence, whilst enhancing physical qualities critical to sport.